2023
DOI: 10.1155/2023/2502314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Smear-Positive Pulmonary Tuberculosis and Associated Factors among Patients Visiting Health Facilities of Gedeo Zone, Southern Ethiopia: A Cross-Sectional Study

Abstract: Introduction. Tuberculosis (TB) was one of the top causes of ill health and the leading cause of deaths worldwide until the coronavirus (COVID-19) pandemic. Hence, this study is aimed at assessing the prevalence of sputum smear-positive TB and associated factors among TB-suspected patients attending in Gedeo Zone health facilities, Southern Ethiopia. Methods. A facility-based cross-sectional study was conducted among 220 TB-suspected patients in Gedeo Zone health facilities from July 01 to Sep 30, 2021. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…In another study conducted by Yohanes et al [1], the overall incidence of smear-positive pulmonary TB was 14.2% among 113 suspects of pulmonary TB who had a cough for more than 2 weeks. Mantefardo et al conducted a similar study on 220 suspect pulmonary TB patients and found a sputum positivity rate of 18.2% which is close to our study [2]. The total number of males in our study was significantly more than females (66.27% vs. 33.72%) highlighting the fact that male patients were more likely to present with symptoms of pulmonary TB, and hence, most sputum samples that were sent for analysis were of male patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In another study conducted by Yohanes et al [1], the overall incidence of smear-positive pulmonary TB was 14.2% among 113 suspects of pulmonary TB who had a cough for more than 2 weeks. Mantefardo et al conducted a similar study on 220 suspect pulmonary TB patients and found a sputum positivity rate of 18.2% which is close to our study [2]. The total number of males in our study was significantly more than females (66.27% vs. 33.72%) highlighting the fact that male patients were more likely to present with symptoms of pulmonary TB, and hence, most sputum samples that were sent for analysis were of male patients.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of patients presenting to the respiratory outpatient department of medical college in India are TB patients. There is a rising incidence of multidrugresistant (MDR) TB cases the causes of which are multi-factorial [2]. The aim of this study was to estimate the sputum acid-fast bacilli (AFB) smear positivity rate and also the prevalence of MDR TB cases among patients suspected to have pulmonary TB presenting to tertiary care hospital in Southern Rajasthan.…”
Section: Introductionmentioning
confidence: 99%